EXPECTATIONS AND REALITY: VIDEO GAMES IN EDUCATION FROM TEACHERS' PERSPECTIVE - Alqurashi, Mohammed; Williams, Mia Kim (PEOPLE: International Journal of Social Sciences, 2019)
Games integration could be a catalyst for changing pedagogical practices. however, the effectiveness of using video games in education depend on teacher’s acceptance to use video games in their classroom. The purpose of this quantitative study was to investigate Saudi teachers’ perspective toward video game integration in education at elementary, middle, and high schools’ levels in Saudi Arabia; and found differences in teachers’ attitudes between gender and teachers experiences and level of teaching. It also investigated relationships between teachers’ philosophy based on three main learning theories (behaviorism, cognitivism, and constructivism) and their perspectives toward video game use in the classroom. There were 930 male and female teachers who participated in the study. Overall, the results of this study showed Saudi teachers’ attitudes toward video games were fairly positive. Analysis found a relationship between teachers’ philosophy of teaching and their perspectives toward using video games in their classroom for learning. A moderate negative correlation was found between behaviorist philosophy and teachers’ attitudes. On the other hand, there was a moderate positive correlation between cognitivism and constructivism philosophies Saudi teachers’ attitudes toward using video games in classrooms.